The Right to Legal Defense and Efficiency of Criminal Proceedings - Kolaković-Bojović, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
Start implementation of the new Criminal Procedure from 2011 in all criminal courts in the Republic of Serbia, not only brings with it a change of the legislative framework governing the right to a legal defense of the accused, but sheds a completely new light on the role of defense counsel in criminal proceedings, even in those segments which are the normative level remained unchanged in compared to the solutions contained in the Code of Criminal Procedure in 2001. With this in mind, the paper specifically addressed issues like expanding the borders of mandatory defence, attempts to impose special requirements that the lawyer should meet, and the impact of the introduction of prosecutorial investigation and pre-trial hearing on the effectiveness of the criminal proceedings, in light of the rights of the legal defence, that (non) existence can significantly define not only the future course, but also the entire outcome of the criminal proceedings.